Judges' Considerations in the Determination of Marriage Dispensation in Court as a Form of Protection of Children's Rights - Dina Triana Febriana; Sonny Dewi Judiasih; Djanuardi (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
Marriage is the right of every human being to build a family. To provide protection to each party, the state through the government stipulates the Marriage Law as a regulation to create order. So that people who want to get married are required to fulfill the requirements and provisions in the Marriage Law, so that marriage can be said to be legal in religion and the state. The research method used is the juridical-normative method with descriptive-analytical research specifications, with the data collection technique used, namely library document studies. The results of the study include that the judge in determining whether to grant or refuse to grant marriage dispensation to children who will enter into marriage underage is based on consideration of all aspects, both positive and negative impacts of the determination of marriage dispensation. Therefore, the judge carefully considers the best interests of the child and the aspect of danger or disadvantage to the child if the underage marriage is allowed to take place, and also the danger or disadvantage that will arise if the application for dispensation to marry the child is rejected.